A Novel Densovirus Isolated From the Asian Tiger Mosquito Displays Varied Pathogenicity Depending on Its Host Species - Li, Jing; Dong, Yunqiao; Sun, Yan; Lai, Zetian; Zhao, Yijie; Liu, Peiwen; Gao, Yonghui; Chen, Xiaoguang; Gu, Jinbao (Frontiers in Microbiology, 2019)
Mosquito-borne viral diseases (MBVDs) continue to pose a significant global public health burden. Mosquito control remains a core intervention strategy to reduce the transmission of MBVDs. Mosquito densoviruses (MDVs) are mosquito-specific entomopathogenic viruses, and their attractive biological and pathogenic characteristics make MDVs potential biological control agents. However, different viral strains vary greatly in their pathogenicity against different mosquito species, which poses an obstacle for the wide application of MDVs in vector control. In this study, a novel Aedes albopictus densovirus-7 (AalDV-7) was isolated from Aedes albopictus in the dengue-endemic area of Guangzhou, China. The genome of AalDV-7 was cloned and sequenced, and the transcription and translation of three open reading frames (ORFs) were characterized. Phylogenetic analysis indicated that AalDV-7 clustered with MDVs mostly isolated from indigenous mosquitoes. The pathogenicity of AalDV-7 to Ae. albopictus, Aedes aegypti and Culex quinquefasciatus larvae was completely different, and the LD50 of AalDV-7 in Ae. albopictus which was 109.48 genome equivalents per ml (geq/ml) was 12 and 46 times more toxic than those in Ae. aegypti (1010.56 geq/ml) and Cx. quinquefasciatus (1011.15 geq/ml). Furthermore, the LT50 value in Ae. albopictus (7.72 days) was 25% and 26% shorter than those in Ae. aegypti (10.24 days) and Cx. quinquefasciatus (10.42 days) at a titer of 1011 geq/ml. Furthermore, the mortality of AalDV7-infected mosquitoes increased in a dose-dependent manner, and the highest mortality was found in Ae. albopictus larvae infected with 1011 geq/ml AalDV-7 (82.00%). Sublethal effects analysis also showed that AalDV-7 infection significantly decreased pupation and emergence rates. The 1st-2nd instar larvae of all three mosquito species showed a near 100% infection rate, and the highest relative vial titer (305.97 ± 67.57 geq/ng) was observed in Cx. quinquefasciatus. These pathogenic characteristics make AalDV-7 a potential flavivirus control agent in China, whereas its negligible pathogenicity and high infection rate and viral titer in vivo make it a good candidate for gene delivery vectors in Cx. quinquefasciatus gene function analysis. In conclusion, the continuous discovery and isolation of new MDVs enrich the pool of entomopathogenic viruses and provide a variety of choices for optimal MDVs to target certain mosquitoes.